ANALISIS PENGARUH KEBIASAAN MEMBACA BUKU DALAM MENDUKUNG PERKEMBANGAN SOSIAL EMOSIONAL SISWA SEKOLAH DASAR - Putri Ismaya; Arifin Maksum; Anggit Aruwiyantoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The problem raised in this study is to analyze how the habit of reading books influences the social and emotional development of elementary school students. This study uses a literature study method using various reference sources which are then collected and analyzed related to social and emotional development, reading interest, and children's reading habits. The method used emphasizes that reading as a routine activity can help the development of children's social and emotional abilities through understanding moral values, empathy, and emotional management. The results of the study show that the habit of reading, especially with reading materials that have social and emotional value, can help children interact better, manage stress, improve academic achievement, and create better character. This study confirms that family, school, and environment are very important for fostering interest in reading and integrating social and emotional literacy into the learning process. In closing, building a reading habit supported by a good environment is very important to ensure optimal social and emotional development in elementary school children. Keywords: Reading Habits; Development; Social Emotional.